The Bright Revolution: Accelerating Adoption of Solar Energy in India’s Dynamic Landscape - Chawla, Udit; Mohnot, Rajesh; Fadahunsi, Akinola; Mulchandani, Devika (International Journal of Energy Economics and Policy, 2024)
This research paper delves into the global shift towards sustainable energy, focusing on the substantial energy consumption and greenhouse gas emissions of the agricultural sector. Emphasizing the need for cleaner energy sources, particularly solar technology, the study scrutinizes the cases of India to unravel the complexities influencing the adoption of solar technology in diverse socio-economic landscapes. The paper aims to contribute to the ongoing conversation about energy transition, providing a nuanced understanding of challenges and opportunities associated with widespread solar technology deployment. Focusing on solar technology as a transformative solution, the paper explores adoption and integration challenges, considering India as a case study due to its abundant solar resources. The research examines technological, economic, social, and institutional forces to illuminate the potential of solar technology in shaping sustainable and inclusive energy landscapes. The paper underscores the importance of community support for renewable energy projects and addresses material and attitudinal influences. Geographical location, government policies, and awareness campaigns are identified as critical elements for successful solar technology integration.